PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN MOBIL MPV MEREK MITSUBISHI XPANDER DI KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The Mitsubishi Xpander Brand MPV car is a motorized vehicle product thatappeared in Indonesia in 2017. The purpose of this study was to determine the effect ofproduct quality and brand image on the purchase and satisfaction decisions of theMitsubishi Xpander MPV brand in Pekanbaru. This study uses Customer Satisfaction asan endogenous variable and Purchasing Decision as an intervening variable. While theexogenous variables in this study are Product Quality and Brand Image. The populationin this study were 748 people and the number of samples used in this study was 173people. This research uses Probability sampling technique in determining researchrespondents. Data taken from respondents using a questionnaire. The analysis methodused in this study is path analysis using the SPSS application 24 (Statistical Package ForSocial Science). The results of this study indicate that product quality and brand imagehave a positive and significant effect on purchasing decisions. Purchasing decisions havea positive and significant effect on Consumer Satisfaction. Product Quality and BrandImage have a positive and significant effect on Consumer Satisfaction through aPurchasing Decision. Brand Image has a stronger influence than Product Quality inachieving the Purchasing Decision and Consumer Satisfaction of the Mitsubishi XpanderBrand MPV Car.Keywords: Product quality, Brand Image, Buying Decision, Costumer Satisfaction.